A late medieval farmstead at Corsankell, near Stevenston, North Ayrshire. Issue 1 (March 2015) - Atkinson, Dan; Brown, Graeme; Cross, Morag; Taylor, Simon; Franklin, Julie
Abstract : Historical, placename and archaeological evidence have been brought together at Corsankell Farm to indicate that the search for medieval settlement in the west of Scotland can bear fruit. Archaeological excavation found evidence of later medieval settlement remains, and the historical and placename research suggests a date for the settlement of Corsankell back into the 12 th century or earlier. The focus of the settlement has shifted at least twice in the history of Corsankell, and physical remains from the 12 th century were not found, but this work demonstrates that medieval settlement can be revealed by examining modern-day farms.